New hybrid sol-gel coating for solid phase Microextraction - Lee, Siew Ling (Faculty of Science, Universiti Teknologi Malaysia, 2009)
A new 2-hydroxymethyl-18 crown-6 and polydimethylsiloxane (2OHMe-18C6/PDMS) hybrid fiber coating for solid phase microextraction (SPME) was prepared using sol-gel technology with methyltrimethoxy-silane (MTMOS)as precursor and hydroxy-terminated polydimethylsiloxane(OH-TPDMS) and 2OHMe-18C6 as coating material. Three different compositions of sol-gel were used to synthesize three different 2OHMe-18C6/PDMS hybrid and its extraction capabilities towards three selected organophosphorus pesticides, OPPs namely chlorpyrifos, diazinon and profenofos was assessed and compared to commercial 100 Î¼m PDMS fiber. All three sol-gel compositions used showed superior extraction performances towards the selected OPPs compared to the commercial SPME fiber. The successful binding of 2OHMe-18C6/PDMS was confirmed from Fourier Transform Infra Red Spectroscopy (FT-IR). Field emission-scanning electron micrograph (FESEM) of the three hybrid coated fiber showed a non-homogeneous to homogenous surface. The new hybrid coating material had excellent thermal stability up to 350Â°C. Limits of detection of the OPPs using the newly developed sol-gel 2OHMe-18C6/PDMS hybrid SPME fiber coupled with gas-chromatography-electron capture detector (GC-ECD) is in the range of 7-39 Î¼g/L. Sol-gel coating technology offers a promising technique to vary the compositions of the sol-gel components to produce materials with different selectivity and performance.